Prevalence and Risk Factors of Cerebral Microbleeds: Analysis From the UK Biobank. (12th October 2021) - Lu, Dongwei; Liu, Junfeng; MacKinnon, Andrew D.; Tozer, Daniel J.; Markus, Hugh S.
Abstract : Background and Objectives: To determine the prevalence of and risk factors for cerebral microbleeds (CMBs) at different locations in a large healthy community population. Methods: A total of 8, 159 participants from the UK Biobank with MRI scans suitable for CMB analysis were included. Brain susceptibility-weighted imaging data were acquired on 2 identical 3.0T scanners. The Microbleed Anatomical Rating Scale was used to identify definite CMBs. Generalized linear models were used to determine independent associations with all CMBs and lobar, deep, and infratentorial CMBs. Results: The mean age at scan was 62.1 ± 7.4 years. One or more definite CMBs were detected in 572 (7.0%) participants. Of those with CMBs, 439 (76.7%) had lobar CMBs, 103 (18.0%) had deep CMBs, and 83 (14.5%) had infratentorial CMBs. Age was an independent risk factor for CMBs in all locations. APOE4 and male sex were positively associated and higher body mass index was negatively associated with lobar CMBs. Hypertension, smoking, and alcohol consumption were associated with deep CMBs, but not with lobar CMBs. Only age was associated with infratentorial CMBs. The associations were unchanged after controlling for white matter hyperintensity lesion volume as a marker of small vessel disease severity. Discussion: In this large population-based study, CMB prevalence detected using a low sensitivity and high specificity system was 7%. There were distinct risk factor profiles for CMBs in lobar and deep locations consistent with different underlying pathophysiologic processes. Trial Registration Information: Clinical Trial registration number: UK Biobank application number 19463.